SEX EDUCATION FOR KIDS MENGGUNAKAN MEDIA VIDEO DAN POSTER DI SD NEGERI 3 SERANGAN - Ariyanti, Kadek Sri; Batiari, Ni Made Padma; Saraswati, Anak Agung Sagung Ratu Putri; Kencana, Ni Luh Putu Putri; Kurnianingsih, I Desak Ketut Dewi Satiawati (Universitas Mataram, 2025)
Introduction: Delivering sexual health information to children needs to be packaged in an interesting and easy-to-understand way. Visual media, such as videos and posters, have the advantage of conveying information in an interesting and interactive way. Objective: to provide accurate and comprehensive knowledge about sexual health to children. Method: The activity was carried out on Thursday, January 23, 2025, at Serangan 3 Public Elementary School. The target of the activity was 40 students in grades IV, V, and VI. The method of implementing the activity was qualitative by providing a pre-test through interviews, then providing interventions through educational videos and posters about sexual health in children with a duration of approximately 10 minutes. Evaluation was carried out by providing a post-test through interviews. The indicator of the success of the activity was that students managed to answer more than 50% of the questions given correctly. Results: Interviews in the pre-test showed that students managed to answer an average of 1-2 of the 6 questions given correctly. There was an increase in interview results during the post-test, where on average students managed to answer 4-5 of the 6 questions given correctly. Conclusion: The use of videos and posters in sex education for children can improve children's understanding of sexuality. Educators and parents need to work together to design sex education materials that are appropriate to the age and needs of children.